Neutrophil alkaline phosphatase in pregnancy - Beal, R. W. (1967)
Neutrophil alkaline phosphatase levels have been studied in a group of 194 pregnant women, using a modified technique which permits more rapid counting of the required number of neutrophils with a degree of consistency comparable with standard methods. No correlation was found between neutrophil alkaline phosphatase levels and the period of gestation; in contrast to previous findings, no differences were observed between the means for tests done in early pregnancy and those performed later in pregnancy. There was no demonstrable relationship between neutrophil alkaline phosphatase levels and age, parity, and white cell count. Elevated levels were also observed in women taking oral contraceptives. Thus, although the neutrophil alkaline phosphatase has diagnostic value in certain other disease states, the above findings suggest that it is of little or no value in pregnancy. The possibility of hormonal control of the elevated level of neutrophil alkaline phosphatase seen in pregnancy and simulated pregnancy is discussed, as is the possible relationship to increases in serum alkaline phosphatase in pregnancy.